2013
DOI: 10.1021/es3033007
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emissions and the Interrelation of Urban and Forest Sectors in Reclaiming One Hectare of Land in the Pacific Northwest

Abstract: The interrelation between urban areas and land use options for greenhouse gas mitigation was evaluated by assessing the utility of urban residuals for soil reclamation. Long-term impacts on soil C storage for mine lands restored with urban organic residuals were quantified by sampling historic sites reclaimed both conventionally and with residuals-based amendments. Use of amendments resulted in greater C storage compared to conventional practices for all sites sampled, with increases ranging from 14.2 Mg C ha(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…2). This is a higher rate of soil C retention of land applied biosolids than the 25 Mg CO 2 per 100 Mg dry biosolids previously observed and modeled (Brown et al, 2010), but lower than the 140 Mg CO2e per 100 Mg dry biosolids estimated by Trlica and Brown (2013). If only stable C, as represented by nonhydrolyzable C, is credited for C sequestration, then the 0.34 Mg C in soil per Mg of added C in biosolids (0.07 Mg C per Mg dry biosolids; 25 Mg CO 2 e per 100 Mg dry biosolids) rate of C accumulation should be used, a value that is in accordance with Brown et al (2010).…”
Section: Resultsmentioning
confidence: 49%
“…2). This is a higher rate of soil C retention of land applied biosolids than the 25 Mg CO 2 per 100 Mg dry biosolids previously observed and modeled (Brown et al, 2010), but lower than the 140 Mg CO2e per 100 Mg dry biosolids estimated by Trlica and Brown (2013). If only stable C, as represented by nonhydrolyzable C, is credited for C sequestration, then the 0.34 Mg C in soil per Mg of added C in biosolids (0.07 Mg C per Mg dry biosolids; 25 Mg CO 2 e per 100 Mg dry biosolids) rate of C accumulation should be used, a value that is in accordance with Brown et al (2010).…”
Section: Resultsmentioning
confidence: 49%
“…Calgaro et al (2008) observed an increase in chemical attributes (OM, P, pH, K, SB, CEC, and V %) when E. crassipes was applied. The use of this or other residues have been reported to be beneficial for degraded areas as organic or microbial fertilizers supporting revegetation (Trlica and Brown, 2013). Pavinato and Rosolem (2008) noticed that residues from vegetation improve the Ca, Mg and K content.…”
Section: ) -----------% -------------------(Mg Dm -3 ) --------mentioning
confidence: 99%
“…As the importance of and potential for establishing these sites as functional ecosystems is increasingly recognized, it is likely that traditional measures of soil fertility, quality, and productivity will be included in tools to evaluate amendment mixtures and remedial options. Long-term sites where disturbance rather than metal contamination was the primary factor limiting plant growth (e.g., coal mine sites) have shown that amendments are sufficient to reestablish productivity [19,45]. It is likely that similar results will be seen with the appropriate use of amendments.…”
Section: Soil Fertility and Physical Propertiesmentioning
confidence: 99%
“…Many of these benefits have been realized at disturbed noncontaminated sites restored with residuals. For example, high rates of carbon sequestration have been observed on sites reclaimed with organic residuals in comparison to sites restored with topsoil or fertilizer [19,45,77]. US EPA sampled contaminated sites restored with amendments to quantify soil carbon restoration [76].…”
Section: Quantification Of Valuementioning
confidence: 99%